PT FACIES OF ELEMENTARY, HYDROCARBON, AND ORGANIC SUBSTANCES IN THE C-H-O SYSTEM - Marakushev A.A.; Marakushev S.A. (My University, 2006)
The substances in the C–H–O system are subdivided into elementary (O2, H2, H2O, C, CO, CO2, CH4) and composite (hydrocarbons and organic compounds) varieties. The composite substances fit into the system of elementary substances and are located on tie lines that connect their compositions. Owing to this, the three-component system C–H–O is divided into two-component subsystems where hydrocarbons and organic compounds are formed from elementary substances autonomously. The compositions of some organic substances are located at the tie line intersections, which determine their belonging to two (HCOOH) or even three (CH2O) subsystems. Formaldehyde CH2O and some of its stoichiometric polymers occupy a central position among organic compounds.